Gambaran Pengetahuan dan Pola Makan Remaja Putri Penderita Dismenore - Faradina, Fenny; Nirmala, Intan Ria; Nurlaela, Euis (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Introduction and Methods Primary dysmenorrhea is a common complaint experienced by adolescent girls, and dietary patterns are suspected to be one of the contributing factors affecting its severity. This study aims to examine the dietary habits and nutritional knowledge of adolescent girls in relation to the occurrence of primary dysmenorrhea. Specifically, it seeks to answer whether imbalanced eating patterns contribute to the severity of menstrual pain in adolescents. A quantitative study with a cross-sectional approach was conducted at SMA Negeri 1 Kendari City between February and March 2024. A total of 41 adolescent girls were selected using a stratified random sampling technique. Data were collected through a menstrual pain questionnaire, a balanced nutrition knowledge questionnaire, and a Food Frequency Questionnaire (FFQ). Results A total of 97.6% of respondents were aged 15–16 years. The majority experienced moderate (51.2%) and mild (36.6%) dysmenorrhea. The level of nutritional knowledge was moderate (41.5%) and low (46.3%). A total of 51.2% of respondents had poor dietary patterns. Among those with mild dysmenorrhea, 66.7% had poor eating patterns; among those with controlled severe dysmenorrhea, 60% had poor eating patterns; and among those with moderate dysmenorrhea, 61.9% had moderate dietary patterns. Respondents with good nutritional knowledge mostly (80%) had moderate dietary patterns. Conclusion and Recommendations The findings indicate that inadequate nutritional knowledge and imbalanced dietary intake among most respondents—across all categories of dysmenorrhea severity—may contribute to the intensity of menstrual pain. Educational and nutritional interventions are recommended through collaborative efforts involving multiple stakeholders. Further research is needed with broader variables to explore the influence of social, economic, and cultural factors on the management of dysmenorrhea in adolescents. Contribution to the Sustainable Development Goals (SDGs) This study aims to explore the incidence of dysmenorrhea among adolescent girls in relation to their knowledge and dietary patterns. The article contributes to Sustainable Development Goal (SDG) 3: Ensure healthy lives and promote well-being for all at all ages. Specifically, it supports Target 3.4, which aims to reduce by one-third premature mortality from non-communicable diseases through prevention and treatment, and to promote mental health and well-being.